The Impact of the Digital Sharing Economy on the Saving and Investment Patterns of Generation Z in Iran - Zandi, Mohammad Amin; Zandi, Mohammad Ehsan; Mansouri, Mostafa (AI and Tech in Behavioral and Social Sciences, 2026)
The digital sharing economy, as an emerging paradigm, profoundly shapes the financial behaviors of Generation Z and transforms traditional patterns of saving and investment. This study investigates the impact of the digital sharing economy on the saving and investment styles of Generation Z in Iran, focusing on predictive factors such as psychological factors, technological factors, and demographic variables. The research follows a descriptive correlational design with a structural equation modeling (SEM) approach. The statistical population consisted of Generation Z users (born between 1997 and 2012) of sharing economy platforms in Iran, among whom 384 participants were selected through convenience sampling. Data were collected via a questionnaire with a composite reliability above 0.7 for all constructs and were analyzed using path analysis and standardized coefficients. The results indicated that technological factors were the strongest predictors of risk-taking investment style (β = 0.508), while psychological factors were the most significant determinants of conservative saving style (β = 0.443). Demographic factors showed a significant negative relationship with both investment (β = −0.318) and saving styles (β = −0.233). The digital sharing economy had a weak effect on saving style (β = 0.184) and a negligible effect on investment style (β = 0.069). The model explained 31.7% of the variance in investment style and 42.5% of the variance in saving style. The findings revealed a fundamental duality in the drivers of Generation Z’s financial behavior: investment is technology-driven, whereas saving is rooted in psychological contexts. Contrary to expectations, the youngest members of Generation Z are the pioneers of digital financial transformation, while the sharing economy, despite its quantitative growth, plays a limited role in shaping financial behaviors. These results highlight the necessity of adopting differentiated approaches for promoting investment (through technological infrastructure development) and saving (through fostering trust and education).